2022
DOI: 10.3390/robotics11040074
|View full text |Cite
|
Sign up to set email alerts
|

Toward Avoiding Misalignment: Dimensional Synthesis of Task-Oriented Upper-Limb Hybrid Exoskeleton

Abstract: One of the primary reasons for wearable exoskeleton rejection is user discomfort caused by misalignment between the coupled system, i.e., the human limb and the exoskeleton. The article focuses primarily on the solution strategies for misalignment issues. The purpose of this work is to facilitate rehabilitative exercise-based exoskeletons for neurological and muscular disorder patients, which can aid a user in following the appropriate natural trajectory with the least amount of misalignment. A double four-bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…On the one hand, non-anthropomorphic designs refer to exoskeletons that violate their most widespread definition [17]: "an exoskeleton is an external structural mechanism with joints and links corresponding to those of the human body". For example, recent works based on a modular synthesis approach have led to the introduction of two four-bar mechanisms in series to design an upper limb exoskeleton [18,19]. Overall, numerous designs have been proposed for the main joints of both the upper [20][21][22] and lower [23][24][25][26][27] human limbs.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, non-anthropomorphic designs refer to exoskeletons that violate their most widespread definition [17]: "an exoskeleton is an external structural mechanism with joints and links corresponding to those of the human body". For example, recent works based on a modular synthesis approach have led to the introduction of two four-bar mechanisms in series to design an upper limb exoskeleton [18,19]. Overall, numerous designs have been proposed for the main joints of both the upper [20][21][22] and lower [23][24][25][26][27] human limbs.…”
Section: Introductionmentioning
confidence: 99%
“…The exoskeleton model must meet the convenience and adjustment of the rehabilitation robot. In the last decade, several studies have shown the development of research on the structural design of exoskeleton rehabilitation robots to help post-stroke patients [10], [11]. The result was due to the different mechanical structures and rehabilitation principles.…”
Section: Introductionmentioning
confidence: 99%